Field lab on internationalization: a case study of a Portuguese SME in the floor covering industry - Martins, Mariana Oliveira De Almeida (2021)
Company X is a growing Portuguese SME operating in the floor covering industry as a wholesaler. The company intends to expand globally and consolidate its financial stability after experiencing a deep crisis and downsizing its business. This dissertation’s purpose is to develop realistic guidelines for Company X to successfully implement an internationalization strategy. To formulate the final recommendation, both company and sector were analyzed, as well as macro and industry-specific dimensions that resulted in a shortlist of five potential target countries. A detailed evaluation of each country allowed for the selection of Denmark as the optimal destination. Ultimately, a comprehensive marketing plan and the project’s financial implications reflected the direct exporting strategy to be executed by the company.